A service-free wireless sensor solution - Vinodthan, Murugaya (2016)
Energy harvesting has become a vital part of the global energy demand where renewable ambient energy is converted into electrical energy to provide power to meet certain global needs. The project aims to develop a service free sensor and intergrate it with an energy harvesting device to provide a cheaper alternative to expensive security installations. The report will discuss various energy harvesting devices and its suitability for this project. The system aims to improve the security of homes and other closed environments at an affordable price. The report will consist of work procedure of the project that includes, research, design process and finally testing and evaluation.